Pemberdayaan Masyarakat Melalui Pondok Kreatif Sebagai Ruang Inspiratif Anak-Anak Desa Karang Indah Kabupaten Barito Kuala - Adistya Karamina Fasyah; Varinia Pura Damaiyanti; Rizky Ircham Muzaki; Aliya Putri; Syifa Sophia Nurmasitha; Neli Rahmawati; Muhammad Fadhil; Dyllan Raditya Dienova (Prodi Sosiologi FISIP ULM, 2023)
Pondok Kreatif is a community empowerment project that aims to stimulate change in the children of Karang Indah Village to become more creative and innovative individuals. This is based on the findings of problems analyzed through social mapping of Karang Indah Village, Mandastana Sub-District, Barito Kuala Regency. The problem that occurs in the children of Karang Indah Village is that they become passive because they are concerned with playing online games and social media. The service team created a solution by forming the